Catalan Virgin Olive Oil Protected Designations of Origin: Physicochemical and Major Sensory Attributes. Issue 3 (18th January 2019) - Vichi, Stefania; Tres, Alba; Quintanilla‐Casas, Beatriz; Bustamante, Julen; Guardiola, Francesc; Martí, Esteve; Hermoso, Juan F.; Ninot, Antonia; Romero, Agustí
Abstract : Catalonia, located in the northeast of Spain, comprises five extra virgin olive oil (EVOO) protected designations of origin (PDOs). Despite the proximity between them, these PDOs represent unique pedoclimatic conditions and traditional olive cultivars that are briefly reviewed in the present manuscript. In addition to the compliance with quality standards fixed by product specifications, EVOOs show singular and distinctive composition and sensory profiles. With the aim to describe the characteristics of Catalan EVOOs, their sensory and analytical traits are reviewed with the support of data collected between 2009 and 2017 in more than 42 milling facilities from the five Catalan PDOs, within the frame of official surveys launched by the Catalan Government. Practical Applications : A detailed knowledge of the characteristics of differentiated‐quality productions will favor their valorization and protection, improving their image and increasing the consumer confidence. For this reason, studies to objectively define the characteristics of PDO EVOOs are useful tools to promote this sector. Despite the proximity between Catalan PDOs, their unique pedoclimatic conditions and traditional olive cultivars contribute to produce extra virgin olive oils with singular and distinctive composition and sensory profiles. Abstract : Despite the proximity between Catalan PDOs, their unique pedoclimatic conditions and traditional olive cultivars contribute to produce extra virgin olive oils with singular and distinctive composition and sensory profiles.